2019
DOI: 10.3357/amhp.5389.2019
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Autonomic Activity in Commercial Aircrew During an Actual Flight Duty Period

Abstract: BACKGROUND: The work schedules of airline crewmembers include extended workdays, compressed work periods, and limited time for recovery, which may lead to cardiovascular strain and fatigue. The aim of this study was to evaluate changes in heart rate variability (HRV) during work and sleep, and with respect to work characteristics and breaks.METHODS: We followed 49 airline crewmembers during four consecutive workdays of ≥39 h. Data included HRV measurements, a questionnaire, and sleep/work diaries. HRV paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 63 publications
2
8
1
Order By: Relevance
“…Moreover, severely fatigued pilots had higher rates of excessive daytime sleepiness, depression and obstructive sleep apnea than non-fatigued pilots ( O’Hagan et al, 2018 ). Levels of cardiovascular strain were found to be higher on day 4 than on day 1 of a work period, consistent with the hypothesis that fatigue and work periods increase cardiac strain among aircrew ( Goffeng et al, 2019a ). These long-term detrimental effects of circadian rhythm disruption and fatigue have also been observed in other occupational areas.…”
Section: Effects Of Fatiguesupporting
confidence: 86%
“…Moreover, severely fatigued pilots had higher rates of excessive daytime sleepiness, depression and obstructive sleep apnea than non-fatigued pilots ( O’Hagan et al, 2018 ). Levels of cardiovascular strain were found to be higher on day 4 than on day 1 of a work period, consistent with the hypothesis that fatigue and work periods increase cardiac strain among aircrew ( Goffeng et al, 2019a ). These long-term detrimental effects of circadian rhythm disruption and fatigue have also been observed in other occupational areas.…”
Section: Effects Of Fatiguesupporting
confidence: 86%
“…Although a positive correlation between workload and mental fatigue level has been reported (Arsintescu et al, 2020), they may cause the opposite effect on operators; for example, fatigue generally causes decreased alertness, but workload may induce higher arousal and vigilance (Arsintescu et al, 2020; Kinney & O'Hare, 2020). Although most previous studies reported a decreased SDNN under mental fatigue, indicating enhanced mental stress (Cao et al, 2019; Castaldo et al, 2015; Goffeng et al, 2019), SDNN in this study was found to increase significantly. A possible interpretation is that participants' stress got relieved when they became increasingly familiar with the experimental settings, causing interference to the mental fatigue consequences.…”
Section: Discussioncontrasting
confidence: 81%
“…Specifically, LF, LFnu, and LF/HF significantly increased, while HFnu significantly decreased. Similar results have also been reported in fatigued pilots who performed prolonged flight tasks or stayed awake for lengthy hours (Alaimo et al, 2020; Cao et al, 2019; Cheng et al, 2018; Goffeng et al, 2019; Mansikka et al, 2016). Although LF may reflect both sympathetic and parasympathetic activity, LFnu and LF/HF can specifically reflect sympathetic tone (Castaldo et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations